Review of Intraocular Pharmacokinetics of Anti-Infectives Commonly Used in the Treatment of Infectious Endophthalmitis - Andrea Luaces-Rodríguez; Miguel González-Barcia; María José Blanco-Teijeiro; María Gil-Martínez; Francisco Gonzalez; Francisco Gómez-Ulla; María-Jesús Lamas; Francisco-Javier; Anxo Fernández-Ferreiro (MDPI AG, 2018)
Although intravitreal administration of anti-infectives represents the standard treatment for infectious endophthalmitis, the knowledge about their pharmacokinetics is still limited. In this review, we aimed to summarise the factors influencing the pharmacokinetics of the anti-infective agents. We have conducted a comprehensive review of the preclinical pharmacokinetic parameters obtained in different studies of intravitreal injections of anti-infectives performed on animals, mainly rabbits. The two aspects with the biggest influence on pharmacokinetics are the distribution in the vitreous humour and the elimination through the posterior segment. The distribution can be affected by the molecular weight of the drug, the convection flow of the vitreous, the condition of the vitreous humour depending on the age of the patient, the possible interactions between the drug and the components of the vitreous, and the presence of vitrectomy. Meanwhile, the elimination includes the metabolism of the drug, the clearance via the anterior and posterior routes, and the possible inflammation of the eye resulting from the disease. Understanding the pharmacokinetics of the anti-infectives used in clinical practice is essential for a correct application. The information provided in this review could offer guidance for selecting the best therapeutic option according to the characteristics of the drugs.